Effect of organoclay and ethylene-octene copolymer inclusion on the morphology and mechanical properties of polyamide/polypropylene blends - Wahit, Mat Uzir; Hassan, Azman; Rahmat, Abd Razak; Lim, Jian Wei; Ishak, Zam Zarina (SAGE publication, 2006)

(untitled)
A series of compatibilized polyamide 6/polypropylene (PA6/PP) blends, of composition 70/30, 50/50, and 30/70 have been prepared in a twin screw extruder followed by injection molding. The four types of PA6/PP blends involved are the neat PA6/PP blends, PA6/PP/ethylene-octene copolymer (polyolefin elastomer, POE), PA6/PP/organoclay, and PA6/PP/POE/organoclay. Tensile, flexural, and Izod impact test are performed on these blends. The morphology of the blends is characterized by scanning electron microscopy (SEM). The mechanical properties of the blends are found to be strongly dependent on the PA6/PP blend ratio. For any blend system, with the increase in PP concentration, the strength and stiffness decreases, while the toughness increases. The incorporation of 4 wt% organoclay into PA6/PP blends significantly increases the modulus and strength but with corresponding reductions in impact strength. Conversely, the incorporation of POE increases the toughness, while the strength and stiffness decrease. However, PA6/PP blends containing both organoclay and POE elastomer are shown to have the potential to be more rigid and tougher than the neat PA6/PP itself. Blend ratio and presence of organoclay are found to influence the morphology (e.g., POE particle size and distribution) of POE toughened nanocomposites systems. A finer particle size and better distribution of POE elastomer has been observed in high PP concentration PA6/PP blends and organoclay filled PA6/PP blends.